Bioactivity of plants gums against pathogenic fungi - Badar, K V; Kakde, Rajendra B; Pawar, S M; Chavan, Ashok M (International Multidisciplinary Research Journal, 2012)
In order to investigate the bioactivity of gum of selected plantsÂ against the economically important fungi like Alternaria alternata, Aspergillus niger, Curvularia lunata, Curvularia pellescence, Fusarium equiseti, Fusarium oxysporum, Macrophomina phaseolina, Penicillium digitatum, Penicillium chrysogenum and Rhizopus stoloniferÂ the experiments were carried out by using different concentrations of plant gum i.e. 1%, 5%, 10%. Gum Acacia arabica was found to promote the growth of fungi like Alternaria alternata, Aspergillus niger as the function of concentration of gum. Whereas the growth of fungi like Curvularia lunata, Fusarium equiseti, Fusarium oxysporum, Macrophomina phaseolina, Penicillium digitatum and Penicillium chrysogenum, were found to be inhibited by the 1% gum of Acacia arabica. But on the contrary the concentration of gum increased to level of 5% and 10%, the increase in dry mycelium weight of these fungi were found. The Rhizopus stolonifer was found to be suppressed at 10% concentration. Gum of Acacia chundra was found to promote the growth of fungi like Macrophomina phaseolina and Penicillium chrysogenum with the increased concentration of gum. On the other hand the fungi like Alternaria alternata, Aspergillus niger, Curvularia lunata, Fusarium equiseti, Fusarium oxysporum and Rhizopus stolonifer were found to be inhibited at 1% concentration of gum. But at 5% concentration the fungi like Alternaria alternata, Aspergillus niger, Curvularia pellecence, Fusarium equiseti and Rhizopus stolonifer showed the increased in dry mycelial weight. At 10 % concentration all fungi except Curvularia pellecence and Penicillium digitatum showed increase in dry mycelium weight. Similarly, gum of Azadirechta indica, Boswellia serrata and Butea monosperma showed fungitoxic activity at variable concentrations.